Efektivitas Penggunaan Media Ranking 1 Dalam Evaluasi Pembelajaran Bahasa Arab Di MA NWDI Bagik Polak - Syafiyahani Sajiddah; Syafiya Hani Sajiddah; Alissa Muwazanatul Hayati; Suparmanto (Lisan An Nathiq : Jurnal Bahasa dan Pendidikan Bahasa Arab, 2023)
Arabic Language is one of the subjects that is less popular and liked by students, as they consider it complicated and with many rules. This causes them to quickly get bored when studying it, and also due to the monotonous learning system resulting from the use of passive media. Therefore, a teacher needs appropriate methods and media to overcome these issues. In this case, the researcher used the ranking 1 game strategy as a learning media to evaluate the Arabic language learning process in schools. The aim of this research is to describe the application of ranking 1 media in evaluating Arabic language learning to eliminate boredom among students, thus creating an effective and efficient learning process. The method used is descriptive qualitative method with field research type, and it employs data reduction and data validity analysis techniques. The research result show that students participate well in the learning process, do not feel bored, actively engage, think quickly, and respond to questions effectively, thus proving its effectiveness when applied in various school levels. The accuracy in implementing the media will have a positive impact on the learning outcomes obtained.